MODERNISASI MU’ALLIMIN - Wardi, Moh. (STAI Ma'had Aly Al-Hikam Malang, 2014)
Modernization of Islamic education as an effort to achieve the ideal of Islamic education was done by Ahmad Madani (1970), a Muslim cleric. Negative connotation of modernization that firstly derived from West, shifted into renewal as it is accepted and appreciated as tajdid. Islamic education modernization occurred in a row of modernization of Islamic thought. In line with the enhancement pretension, an attempt to modernize traditional education that is identical to Muslim world specifically in Indonesia, modernization is needed to fix the practice of Islamic education. This article is purposed to investigate the concepts and ideas of Ahmad Madani in modernizing his institution, Mu'allimin and confirms the relevance of his educational thought